Enhanced metamaterial vibration for high-performance acoustic piezoelectric energy harvesting. (November 2022) - Sun, Weipeng; Zhong, Kexin; Liu, Yuanyuan; Xiao, Hanjie; Zhao, Daoli; Yan, Zhimiao; Tan, Ting
Abstract: The defect states of acoustic metamaterials are utilized for energy confinement and harvesting of acoustic and elastic waves. Previous studies have concentrated on the importance of resonator dynamics in metamaterial energy harvesting. From the perspective of metamaterial piezoelectric dynamics, this letter finds the mathematical relationship between the performance of a two-dimensional acoustic metamaterial energy harvester and the dimension of the metamaterial substrate plate to which the piezoelectric material is attached. It is inferred that the metamaterial substrate should be of optimal thickness to maximize the output power of the energy harvester. Multi-field coupled computational simulations and acoustic energy harvesting experimental studies support the theoretical inference. With the optimal resistance and resonant frequency acoustic incidence, the maximum peak power output by the metamaterial energy harvester with an optimal substrate plate thickness of 0.3 mm is 195.52 μW, which is 6 times and 331 times higher than that of the metamaterial energy harvester with plate thicknesses of 0.4 mm and 0.2 mm, respectively. The findings of this study will help to advance the development of high-performance metamaterial-based acoustic energy harvesters. Graphical abstract: Image 1 Highlights: Vibration of the metamaterial substrate plate is enhanced by optimizing its thickness. Multi-field coupled simulations and acoustic energy harvesting experimental studies support the theoretical inference. The metamaterial substrate should be of optimal thickness to maximize the output power of the energy harvester.